Progress and Research Trends on Catha edulis (Vahl) Endl. (Catha edulis): A Review and Bibliometric Analysis - Ye, Shuang; Hu, Jin; Liu, Zilong; Liang, Man (Frontiers in Pharmacology, 2021)
Catha edulis (Vahl) Endl., known as Catha edulis or Khat, a traditional and regional plant for chewing, smoking or drinking, has placed a worldwide public health problem due to its recent emerging abused consumption. In the face of massive use of Catha edulis, we reviewed related publications to analyze the progress and research trends through bibliometric methods. After screening, a total of 514 scientific literatures published from 1997 to 2020 were included by systematic retrieval from the Web of Science (WoS) database. According to further scientometric analysis, the annual number of publications outputs kept rising in most of the years. Ethiopia and the United States of America (USA) have been devoting significant contributions to the field. Since the research emphasis has been chemical composition, pharmacological and toxicological effects for several years, hot spots were transferred; the mechanism investigations of Catha edulis have been focused in recent years, which might be continued in future. Furthermore, co-operations of multi-disciplinary researches are needed to minimize abuse harms and maximize medicinal benefits of Catha edulis to human beings.